DIFFERENTIAL DIAGNOSIS OF DIGITAL CULTURE IN STARTUP VS NON-STARTUP COMPANIES IN INDONESIA TO DRIVE EMPLOYEE ENGAGEMENT AND DIGITAL MATURITY - Permana, Iman; Afkar, Elvia; Augusta, Helena (UNIVERSITAS PAKUAN, 2021)
Digital transformation is not an easy task to do and many argues that digital culture is one of the many factors contributing to its success. Culture could lead the transformation by collaborating the whole organization towards its mutual vision and therefore could influence the employee engagement. Objective: This study assesses digital cultures role in driving employee engagement and digital maturity when transformation intervention implemented in the organization, specifically in the start-up and non start-ups company in Indonesia. This exploration is intended for managers and leaders to understand the digital culture differences in both group of companies and to determine which opportunities they may need to improve and strengthen the companys employee engagement and digital maturity. Methodology: The combination of Capgeminis digital culture model, Gallup Q12s employee engagement model and Gill VanBoskirks digital maturity model are used in measuring the start-ups and non start-ups. Result: The digital culture score in the start-ups company was higher than in the non start-ups, consistently in all dimensions, with corresponding higher employee engagement as well as digital maturity. Conclusion: This study suggest that the start-ups have a more developed digital culture than the non start-ups. Further research is suggested to find out which dimension of digital culture that would cause a corresponding higher employee engagement and digital maturity. It would be beneficial if the similar study is carried out in a different country so that the comparison of the start-ups culture could be analysed and learned.